CHARACTER AND MULTICULTURAL EDUCATION MODEL FOR GIFTED STUDENTS - M. Muizzuddin (Universitas Islam Malang, 2021)
This article aimed to describe a model for internalizing the values of multicultural Islamic education in Moslem Boarding School with the intention of building social harmony among gifted students. Due to the fact that Moslem Boarding School is an integrated educational institution in Indonesia, it is hoped that Moslem Boarding School will become the basic foundation for alternative education to build a peaceful and harmonious Indonesian society. This study was conducted as a case study in Moslem Boarding School which in practice have instilled the values of multicultural Islamic education. To analyze the event by collecting data through Interview technique, Observation, Documents, Audiovisual And Digital Materials and narrated in the form of qualitative-descriptive with descriptive interpretative analysis. The results of this study indicated that the model for internalizing the values of Multicultural Islamic Education uses Tarbiyah (education) and Taklim (Teaching) Model with Habituation, Exemplary, Emotional, Rational And Functional approaches. involves strategies through habituation and culture, teaches the goodness (moral knowing), feels and loves the kindness (Moral feeling and loving), and teaches the exemplary from the surrounding environment (moral modeling), while the method used is implemented through the yellow book recitation, exemplary Kyai and Ustadz, Spiritual Practice, Lifestyle Habits, Discipline, Organization, Motivation, Scouting, and Sports. Keywords: Multicultural Islamic Education, Moslem Boarding School. Gifted StudentsThis article aimed to describe a model for internalizing the values of multicultural Islamic education in Moslem Boarding School with the intention of building social harmony among gifted students. Due to the fact that Moslem Boarding School is an integrated educational institution in Indonesia, it is hoped that Moslem Boarding School will become the basic foundation for alternative education to build a peaceful and harmonious Indonesian society. This study was conducted as a case study in Moslem Boarding School which in practice have instilled the values of multicultural Islamic education. To analyze the event by collecting data through Interview technique, Observation, Documents, Audiovisual And Digital Materials and narrated in the form of qualitative-descriptive with descriptive interpretative analysis. The results of this study indicated that the model for internalizing the values of Multicultural Islamic Education uses Tarbiyah (education) and Taklim (Teaching) Model with Habituation, Exemplary, Emotional, Rational And Functional approaches. involves strategies through habituation and culture, teaches the goodness (moral knowing), feels and loves the kindness (Moral feeling and loving), and teaches the exemplary from the surrounding environment (moral modeling), while the method used is implemented through the yellow book recitation, exemplary Kyai and Ustadz, Spiritual Practice, Lifestyle Habits, Discipline, Organization, Motivation, Scouting, and Sports. Keywords: Multicultural Islamic Education, Moslem Boarding School. Gifted Students